NET WORKER. - Dellinger, Matt (Smithsonian)
The article profiles Internet researcher Jon Kleinberg, who is a professor of computer science at Cornell University, and teaches a class that examines how opinions, fads and political movements spread through society, and the technology, economics and politics of Web information and online communities. A discussion of Kleinberg's involvement in the development of an influential search algorithm at the IBM Almaden Research Center that ranks the popularity of web sites by measuring how other sites link to them, is presented.